MENINGKATKAN KEMAMPUAN MENULIS PARAGRAF DENGAN STRATEGI MENULIS TERBIMBING (SMT) BAGI MAHASISWA SEMESTER 4 JURUSAN TEKNIK ELEKTRO DI UNIVERSITAS MUHAMMADIYAH MALANG - Sabarun, Sabarun (Jurnal Studi Agama dan Masyarakat, 2008)
The study is aimed at improving the studentsâ writing ability in writing English class using Guided Composition strategy, which refers to a teaching method in which the teacher guides students systematically and orderly in writing a composition. The strategy is selected because it was assumed that the strategy can improve the studentsâ writing ability and motivate the students to actively involve in writing class.The study employs Collaborative Classroom Action Research design. The subjects of the study are three of fourth semester students of the Electrical Engineering Department of Malang Muhammadiyah University of 2006-2007 Academic Years. The study is carried out in two cycles by following the four steps of action research: planning, implementing, observing, and reflecting. Cycle 1 was carried out on February 5th 2007. Meanwhile Cycle 2 was held on Februari 19th 2007. Each cycle consists of one meeting, focused on prewriting activity, whilst writing and post writing activities.The result of this study shows that Guided Composition Strategy is effective in improving the studentsâ paragraph writing ability. It can be seen from the improvement of the studentsâ writing achievement. In the pretest before the implementation of Guided Composition Strategy, the average score of the studentsâ writing achievement was 3.50 in a 1.00 to 6.00 scale. Three students obtained âpoorâ level. However, after Guided Composition Strategy was implemented, the average score of the class in Cycle 1 increased slightly to 4.15. Only two students did not achieve the criteria of success.Â  Then, in Cycle 2, the average score of the class increased dramatically to 4.75, and all subjects achieved the criteria of success. In addition, the students are actively involved in writing class and they are highly motivated to attend the guided writing class.